Anchietea ferrucciae (Violaceae), a new species from the Brazilian Caatinga - de Paula-Souza, J.; Zmarzty, S.; Pirani (Phytotaxa, 2013)
A new species of Anchietea (Violaceae) is described and illustrated. Anchietea ferrucciae is characterized by its 4-carpellate ovary, small flowers and mostly, by its obovate seeds, cuneate at the base, and with a narrow, toothed wing. The new species is narrowly endemic to a very restricted area of the dry Caatinga in Bahia state (Brazil). An identification key to the species of Anchietea is provided.